Investigations of the vascular endothelial factor levels’ changes in experimental diabetic retinopathy - Nataliya Preys; Ivan Savytskyi (Journal of Education, Health and Sport)
Introduction: The paper presents the results of the vascular endothelial growth factor of rats with experimental diabetic retinopathy (DR).